Inter-clausal dependency in Western Tamang - Regmi, Ambika (Nepalese Linguistics, 2019)
Western Tamang, a highly embedding dialect of Tamang, presents an array of inter-clausal dependency (both semantically and syntactically) ranging from most to least exemplified by verbal complements and chained clauses, respectively. In terms of such dependency, subordinate adverbial clauses stand in between verbal complements and chained clauses in Western Tamang. This is, indeed, a typologically interesting phenomenon, especially, in inter-clausal dependency in Bodic languages like Tamang.